Tranexamic Acid in Obstetrics: A Clinical Review - Harvey Vanlalpeka, L Ranjit Singh, Rushulo Khing, Y Ajitkumar Singh (International Journal of Innovative Research in Medical Science, 2016)
Blood loss and subsequent transfusions are associated with major morbidity and mortality. Obstetrics is a bloody business and caesarean section is associated with complications like haemorrhage and problems in subsequent pregnancies. The use of antifibrinolytics can reduce blood loss in surgeries including Obstetrics and Gynecology, and the need for blood transfusion. Tranexamic Acid (TXA), a synthetic lysine-analogue antifibrinolytic, was first patented in 1957 and its use has been increasing in contrast to aprotinin, a serine protease inhibitor antifibrinolytic. The clinical evidence available for TXA therapy in Obstetrics will navigate Obstetrician to develop a better understanding about its applications though still further trials are being conducted for its proper usage and safety. Till date TXA proved to be a promising drug in Obstetrics and other specialities for reducing blood loss in terms of its efficacy and safety profile. However questions regarding clinical effects of TXA, adverse effects and risks necessitate further clinical trials.